Can nutrition support healthy cognitive ageing and reduce dementia risk?. (26th June 2020) - Jennings, Amy; Cunnane, Stephen C; Minihane, Anne Marie
Abstract : Amy Jennings and colleagues describe the evidence and potential for food and food bioactive components to reduce the population prevalence of dementia